Dynamics of Income Inequality and Welfare in Latvia in the Late 1990s - Fofack, Hippolyte (World Bank, Washington, D.C., 2013)
This paper analyzes the dynamics of poverty and income inequality during the recovery phase of the transition that characterized the Republic of Latvia in the late 1990s. Despite a continued rise in income inequality, empirical evidence suggests an improvement in living standards, owing largely to a significant surge in per capita income growth, particularly in urban areas. In a context of rising income inequality and widening urban-rural income and poverty gaps, the benefits of growth were not equally distributed, and poverty persisted in a number of regions (particularly the regions of Latgale and Vitzeme) and among some socioeconomic groups (particularly households deriving their main income from social benefits). In addition to income inequality and asset endowments, poverty appears to be highly correlated with a number of labor market-related variables, particularly unemployment, suggesting that the labor market could be an important transmission channel from growth to poverty. However, though positive, the association between poverty and unemployment is non linear, especially in urban areas, where the labor market and demand are the most important channels of transmission through which growth and macroeconomic development affect household income and living standards.